Degree bounds on homology and a conjecture of Derksen. (21st September 2016) - Chardin, Marc; Symonds, Peter
Abstract : Harm Derksen made a conjecture concerning degree bounds for the syzygies of rings of polynomial invariants in the non-modular case [ Degree bounds for syzygies of invariants, Adv. Math.185 (2004), 207–214]. We provide counterexamples to this conjecture, but also prove a slightly weakened version. We also prove some general results that give degree bounds on the homology of complexes and of $\text{Tor}\, $ groups.